New data on diversity of Notohippidae from the Oligocene of Mendoza, Argentina - Cerdeño Serrano, Maria Esperanza (2014)
Notohippidae (Notoungulata) specimens from the late Oligocene Quebrada Fiera locality Mendoza, Argentina) were previouslyidentified as a new taxon, Mendozahippus fierensis Cerdeño and Vera. New cranial, mandibular, and postcranial remains allow enhancing the description of this species andits ontogenetic variations. The ectocuneiform corresponding to the holotype (MCNAM-PV 4004) of M. fierensis was discovered when reexamining a block belonging to the sediment surrounding the holotype. It matches with the Mt III that was associated with the holotype skull. On the other hand, MCNAM-PV 3851, a badly preserved maxillary fragment, is recognized as a second notohippid taxon, which differs from M. fierensis in the different position and relative size of I3-C. The canine is placed labially to P1 and its section shows a similar size to that of the latter; ahead of the C, the preserved root of I3 is also labially placed, and its section is clearly larger than that of the C. This condition differs from other Deseadan notohippids. Enlargement of the muzzle at the level of I3-C and a developed paracone on premolars are present in Eurygenium and Pascualihippus; the convergence of the premaxillae ahead of I3 in MCNAM-PV 3851 is closer to the condition in Eurygenium. The incompleteness of this specimen, however, prevents its proper definition and it is considered as Notohippidae indet.